The Outcomes of Cemented Femoral Revisions for Periprosthetic Femoral Fractures in the Elderly: Comparison with Cementless Stems - Sponer, Pavel; Korbel, Martin; Grinac, Michal; Prokes, Libor; Bezrouk, Ales; Kucera, Tomas (Clinical interventions in aging, 2021)
Introduction: The present study compares the outcome of the long cemented stem and the revision uncemented stem used in periprosthetic femoral fractures. We propose that the revision with a long stem cemented prosthesis does not compromise fracture healing. Patients and Methods: A consecutive series of 37 patients, operated between 2010 and 2017, were enrolled in a retrospective analysis. A long cemented stem was implanted in 21 patients (study group; age at operation: 63 to 89 years). A distally tapered fluted uncemented stem was used in 16 patients (control group; age at operation: 35 to 77 years). The clinical outcome was evaluated with Merle d'Aubigné and Postel scoring system. Standard radiographs were taken before surgery, at 3, 6, and 12 months postoperatively, and last follow-up. Any and all complications during the follow-up period were recorded. Results: Although a significant difference (P = 0.006) was observed in the post-operative Merle d´Aubigné score over the 12-month follow-up period, no significant difference (P = 0.066) was found in the post-operative pain score between the study and control groups. Periodic radiographic assessments showed the disappearance of radiolucent lines and the diaphyseal part of the fracture was healed in all 34 followed-up cases during the first annual follow-up. Early surgical complications were seen in both groups, the medical complications were observed only in the study group. Conclusion: Based on our results, periprosthetic fractures of the femur after a total hip arthroplasty were associated with significant morbidity and increased mortality in elderly patients. Revision with a long-stem cemented prosthesis provided early pain-free weight-bearing without compromising the healing of femoral fractures in elderly patients with osteoporotic bone, altered mobility, poor balance, and reduced cognitive capacity.
Keywords: Humans; Femoral Fractures; lidé středního věku; Arthroplasty, Replacement, Hip; Periprosthetic Fractures; Aged; periprotetické fraktury; náhrada kyčelního kloubu; senioři; lidé; reoperace; fraktury femuru; Hip Prosthesis; femur; Femur; Middle Aged; Retrospective Studies; Aged, 80 and over; senioři nad 80 let; retrospektivní studie; kyčelní protézy; Reoperation